A comparison of the effects of chlorhexidine and sodium bicarbonate mouthwashes on COVID-19-Related symptoms - Hanieh Karami; Akram Aarabi; Aygineh Hayrabedian; Valiollah Hajhashemi (Wolters Kluwer Medknow Publications, 2024)
Background: Some studies have reported that mouthwashes can decrease the viral load in the mouth, but there is not much information about the effectiveness of mouthwashes on coronavirus disease 2019 (COVID-19). This study was conducted to compare the impact of using two types of mouthwash, chlorhexidine and sodium bicarbonate, on COVID-19 symptoms and infection. Materials and Methods: The present three-group, double-blind clinical trial examined 116 operating room nurses and anesthesia personnel of certain hospitals of Isfahan University of Medical Sciences, Isfahan, Iran. The participants were randomly assigned to three groups: intervention group 1 (chlorhexidine mouthwash), intervention group 2 (sodium bicarbonate mouthwash), and the control group (placebo). Mouthwash was used twice a day (morning and night) for 2 weeks. The participants were monitored in terms of COVID-19-related symptoms for 4 weeks, from the first day of mouthwash use. Results: Fisher's exact test indicated a significant difference between the chlorhexidine and control groups in terms of the onset of COVID-19-related symptoms (p = 0.02). There was no significant difference in the symptoms of COVID-19 between the groups, but the groups were significantly different in terms of all symptoms at a 4-week interval (p = 0.04). Furthermore, headache was less observed in the chlorhexidine (p = 0.007) and sodium bicarbonate (p = 0.03) groups compared to the control group. Conclusions: The use of 0.2% chlorhexidine mouthwash can decrease the onset of COVID-19-related symptoms in health-care workers. In addition, this mouthwash can partially reduce the symptoms of this disease in comparison to the control and sodium bicarbonate groups.